Platelet-Mediated NET Release Amplifies Coagulopathy and Drives Lung Pathology During Severe Influenza Infection - Kim, Seok-Joo; Carestia, Agostina; McDonald, Braedon; Zucoloto, Amanda Z.; Grosjean, Heidi; Davis, Rachelle P.; Turk, Madison; Naumenko, Victor; Antoniak, Silvio; Mackman, Nigel; Abdul-Cader, Mohamed Sarjoon; Abdul-Careem, Mohamed Faizal; et al. (Frontiers in Immunology, 2021)
The influenza A virus (IAV) causes a respiratory tract infection with approximately 10% of the population infected by the virus each year. Severe IAV infection is characterized by excessive inflammation and tissue pathology in the lungs. Platelets and neutrophil recruitment to the lung are involved in the pathogenesis of IAV, but the specific mechanisms involved have not been clarified. Using confocal intravital microscopy in a mouse model of IAV infection, we observed profound neutrophil recruitment, platelet aggregation, neutrophil extracellular trap (NET) production and thrombin activation within the lung microvasculature in vivo. Importantly, deficiency or antagonism of the protease-activated receptor 4 (PAR4) reduced platelet aggregation, NET production and neutrophil recruitment. Critically, inhibition of thrombin or PAR4 protected mice from virus-induced lung tissue damage and edema. Together, these data imply thrombin-stimulated platelets play a critical role in the activation/recruitment of neutrophils, NET release and directly contribute to IAV pathogenesis in the lung.